Germinação de sementes de palmeira Licuri - CAIXETA, Thaíssa Scalco (2018)
The palm trees present economic, ornamental and ecological importance. Licuri is a native ornamental palm uncommonly used and little spread, source of alimentary resources, as fruits, nectar, pollen, produces almond that is consumed in natura. For most species of palm trees, the seedlings production is via seed, so the study of germination is important. The objective of this study was to evaluate the germination of the licuri palm seeds. The treatments consisted of two coconut fiber and vermiculite substrates and four impregnation times 0, 12, 36 and 48 hours, composing a 2x4 factorial totaling 8 treatments with 4 replicates. The seeds were kept in a room with controlled temperature of 25ºC for a total period of 128 days. Better results for germination were observed in the coconut fiber substrate and imbibition at 36 and 48 hours. What the Tetrazolium test is efficient to evaluate the viability of seeds.